Alterations of the P16 gene in uterine cervical carcinoma from Indian patients. Issue 4 (1st June 2003) - Tripathi (Bhar), A.; Banerjee, S.; Roy, A.; Roychowdhury, S.; Panda, C. K.
Abstract : In our analysis, alterations in the P16 tumor suppressor gene were seen in 33% (15/46) of sampled uterine cervical lesions. Among the alterations, mutations in P16 were detected in 15% (7/46) of the samples. One mutation occurred at intron 1/exon 2 splice junction. All the other mutations were in exon 2 with three of them as silent mutations. The promoter hypermethylation and homozygous deletion of P16 gene were detected in 6.5% (3/46) and 8.7% (4/46) of the samples respectively. Loss of heterozygosity and microsatellite size alterations at the P16 locus were seen in 17% (8/46) of the samples. HPV16/18 infection was detected in 76% (35/46) of the samples. But no association was found between P16 alterations and HPV infection. Thus, it seems that P16 inactivation may be associated with the development of some uterine cervical carcinoma.